1998
DOI: 10.1046/j.1365-3024.1998.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Neospora antigens recognized by CD4+ T cells and immune sera from experimentally infected cattle

Abstract: Neospora caninum is recognized as a major cause of infectious abortion in cattle. Very little is known about immunity to Neospora. Cell mediated responses have previously been shown to be important in the development of protective immunity to the closely related parasite Toxoplasma gondii, and may therefore be an important component in the immune response to Neospora. In this paper we report that a group of low molecular weight NCI strain tachyzoite antigens (< or = 30 kDa) separated by SDS PAGE and bound to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…Similarly, the immune response in cattle, as investigated by in vitro studies of peripheral blood cells, is characterized by expression of high levels of IFN-␥ (28,44) by CD4 ϩ T cells (1,28,44). Furthermore, IFN-␥ inhibited intracellular multiplication of N. caninum in culture (17), and Staska et al (39) showed killing of N. caninum-infected autologous targets by CD4 ϩ cytotoxic T cells, indicating that these are likely control mechanisms in vivo.…”
mentioning
confidence: 99%
“…Similarly, the immune response in cattle, as investigated by in vitro studies of peripheral blood cells, is characterized by expression of high levels of IFN-␥ (28,44) by CD4 ϩ T cells (1,28,44). Furthermore, IFN-␥ inhibited intracellular multiplication of N. caninum in culture (17), and Staska et al (39) showed killing of N. caninum-infected autologous targets by CD4 ϩ cytotoxic T cells, indicating that these are likely control mechanisms in vivo.…”
mentioning
confidence: 99%
“…The importance of gamma interferon (IFN-␥) for protection against N. caninum has been well documented in mouse models (1,22,28) and bovine tissue cultures (20,47). The source of this proinflammatory cytokine during bovine neosporosis has been attributed to CD4 ϩ T lymphocytes (26). Parasite-specific cytotoxic T lymphocytes, predominantly of the CD4 ϩ phenotype, have been demonstrated in N. caninum-infected cattle (38).…”
mentioning
confidence: 99%
“…IFN-γ suppressed the parasite growth in brain cells, which agreed with the previous in vitro [13] and in vivo [9,14] studies. In addition, a high concentration of IFN-γ was produced by CD4 + T cells stimulated with Neospora antigen [18], and therefore, IFN-γ may be a critical component of the cell-mediated response to Neospora infection. In studies using T. gondii, murine astrocytes [11], murine microglia [5], human astrocytes [21], human microglia [6] and human endothelial cells [25] activated by IFN-γ inhibited tachyzoite growth.…”
mentioning
confidence: 99%